Abortion as a Muted Reality in Uganda: Narratives of Adolescent Girls’ Agentive Experiences with Pregnancy Termination - Doris M. Kakuru; Jackline Nabirye; Jacqueline Nassimbwa (Youth)
Pregnancy termination, also referred to as abortion, is a contentious subject in many countries. Uganda’s culture requires young people to remain celibate; they therefore suffer from restricted access to any sexual and reproductive health information, products, and services, including contraceptives. Girls who are pregnant in Uganda are oppressed in various ways, including being expelled from school. Since abortion is illegal under Ugandan law, those abortions that take place are assumed to have a high risk of being unsafe. Most previous studies in the African context have thus focused on the phenomenon of unsafe abortion. Adolescent abortion is characterized by a rhetoric of pathology that frames girls as victims of deadly unsafe abortion practices. This paper aims to critique the view that pregnant adolescent girls are merely vulnerable victims who passively accept the denial of SRH services, including abortion. We analyzed the life histories of 14 girls in Uganda who had undergone pregnancy termination. Our findings showed that adolescent girls are not passive victims of the structural barriers to abortion. They use their agency to obtain knowledge, make decisions, successfully terminate pregnancy, and conceal the information as needed. It is therefore important for policymakers to acknowledge the agency of adolescent girls in regard to pregnancy termination and how this recognition could be of benefit in terms of devising appropriate supports for them.